peran penting dewan pengawas syariah untuk lembaga keuangan berbasis syariah - Muhammad Syarofi; Lutfianah Putri (Airlangga Journal of Innovation Management, 2023)
Islamic Financial Institution is an institution that carrying out its financial activities using the principles of Sharia. The Sharia Supervisory Board or Dewan Pengawas Syariah (DPS), a body inside Islamic Financial Institutions, has a responsibility to oversee and advise directors of Islamic Financial Institutions with regard to Sharia principles in doing muamalah. Indonesian Ulama Council (MUI) made a suggestion that the Sharia Supervisory Board (DPS) be established by the General Meeting of Shareholders, which is the entity in charge of overseeing Sharia Financial Institutions. The law governed by the Quran, Hadith, Law No. 21 Article 32 of 2008, and Fatwa DSN_MUI, Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No /Per/M.KUKM/IX/2015, as well as the Bank Indonesia Regulation serve as the foundation for the Sharia Supervisory Board (DPS). The Sharia Supervisory Board has to provide an advice to a Sharia Financial Institution company so that every activity and product issued is in accordance with the principles of Sharia. This study aims to explain and identify the role of Sharia Supervisory Board in Sharia Financial Institution. In its supervision duties, Sharia Supervisory Board should refer DSN's fatwa to ensure that the products issued by Sharia Financial Institutions are in accordance with Islamic provisions. Sharia Supervisory Board members consist of experts in the field of Sharia economics and banking.